The impacts of the “4+7” pilot policy on the volume, expenditures, and daily cost of Serotonin-Specific Reuptake Inhibitors (SSRIs) antidepressants: A quasi-experimental study - Wen, Xiaotong; Wang, Zhaolun; Xu, Luxinyi; Luo, Jia; Geng, Xin; Chen, Xiaoze; Yang, Ying; Cui, Dan; Mao, Zongfu (Frontiers in Pharmacology, 2022)
Objectives: The purpose of this study was to quantitatively evaluate the impacts of the”4 + 7” pilot policy on purchase volume, purchase expenditures, and daily cost and to find the changes in the use of SSRIs. Methods: Data was collected covering 31 months, before, during, and after the “4 + 7” pilot policy was implemented in Shenzhen. Interrupted time-series (ITS) analysis was used to examine whether there had been a significant effect with the onset of the “4 + 7” pilot policy in March 2019. Findings: The daily cost of policy-related drugs had a substantial drop of 2.93 yuan under the “4 + 7” pilot policy. The result has shown a 76.70% increase in volume and a 3.39% decrease in the expenditure on policy-related drugs. This study found that the “4 + 7” pilot policy increased the proportion of purchasing winning drugs, with an increment of 85.60 percent. After the implementation of the “4 + 7” pilot policy, policy-related drugs decreased by 443.55thousand Chinese yuan. The study indicated that volume of winning products significantly increased as shown in the regression with a level coefficient (β2) of -224.17 (p < 0.001) and trend coefficient (β3) of 15.74 (p < 0.001). The result revealed that both volume and expenditures on branded products showed a significant decrease in the regression in the post-intervention period (level coefficient of volume: β2 = -57.65, p < 0.01, trend coefficient of volume: β3 = -3.44, p < 0.01; level coefficient of expenditure: β2 = -712.98, p < 0.01, trend coefficient of expenditure: β3 = -40.10, p < 0.01). Conclusion: The volume-based procurement has successfully led to price reductions and improved the affordability of medicines, especially for those with chronic diseases. The volume-based procurement has demonstrated initial success in reshaping the composition of the Chinese pharmaceutical market in favor of generics with high quality and low prices.